Os impactos psicológicos da violência obstétrica: a percepção de mulheres sobre práticas de violência no parto e seu impacto psicológico - Batista, Beatriz de Souza (Universidade Federal de São Carlos, 2022)
Every day, in Brazil and in the world, many pregnant women are victims of obstetric violence. Despite the lack of a consensus regarding the definition of this concept, many authors tend to define obstetric violence as one or more acts of violence against the parturient woman and her child during obstetric care. With this in mind, the present study addresses the historical, cultural and social process of technological advances and the construction of the interventionist medical posture, which, over the decades, has taken over the protagonism of the parturient in labor and delivery. Also, the main forms of violence suffered by pregnant women in the obstetric context, physical and verbal, are portrayed. Thus, this study seeks to verify and understand the psychological impacts of obstetric violence on women who report having experienced practices of violence during labor and/or childbirth. For this, the participants were screened using the Childbirth Violence Assessment Questionnaire, through which 7 participants were selected to form a focus group. Data analysis was performed using Bardin's (2011) content analysis, aiming to identify existing categories in their speeches and converging ones, referring to the psychological impacts of obstetric violence experienced by these women.
Obstetric violence' psychologycal impacts: women's perceptions about practices of violence during childbirth and its psychological impact
Keywords: Violência obstétrica; Impacto psicológico; Trabalho de parto; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA